IMPROVED METHOD FOR CONSTRUCTING MODELS FOR COMPREHENSIVE ASSESSMENT OF THE RELIABILITY OF THE OPERATION OF ELECTRONIC COMMUNICATION EQUIPMENT OBJECTS WITH COMBINED TIME RESERVE - TYKHONOV, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is devoted to improving the scientific and methodological apparatus for the comprehensive assessment of reliability indicators of electronic communication equipment in modern communication networks. It is determined that the object of theoretical research is the processes of functioning of electronic communication equipment in conditions of limited reliability of software tools. The improved method is intended to build models for assessing electronic communication equipment reliability indicators with different types of failures and a combined time reserve. The initial preconditions, constraints, and assumptions are formulated, under which the problem of constructing models to assess the reliability of electronic communication equipment with a combined time reserve is solved. To achieve the study's goal, it is proposed that the general mathematical model of the functioning of a system with a combined time reserve be decomposed into two interconnected but simpler models that are analysed separately. The first – a model of a regenerating random process –is used to check compliance with the time constraint defined by the replenishable component. Its results are applied in the second model, represented by a three-dimensional Markov process of a special type, which allows the influence of the non-replenishable component of the combined reserve to be considered. The proposed approach allows obtaining new calculation formulas for a comprehensive assessment of the reliability of electronic communication equipment with a combined time reserve, taking into account various types of failures. This allows a more accurate assessment of the reliability indicators of electronic communication equipment and the development of measures to improve them.
Keywords: reliability; communication network; electronic communication equipment; failure; operational parameters; redundancy; efficiency